Epithelial cell alarmin cytokines: Frontline mediators of the asthma inflammatory response - Duchesne, Marc; Okoye, Isobel; Lacy, Paige (Frontiers in Immunology, 2022)
The exposure of the airway epithelium to external stimuli such as allergens, microbes, and air pollution triggers the release of the alarmin cytokines IL-25, IL-33 and thymic stromal lymphopoietin (TSLP). IL-25, IL-33 and TSLP interact with their ligands, IL-17RA, IL1RL1 and TSLPR respectively, expressed by hematopoietic and non-hematopoietic cells including dendritic cells, ILC2 cells, endothelial cells, and fibroblasts. Alarmins play key roles in driving type 2-high, and to a lesser extent type 2-low responses, in asthma. In addition, studies in which each of these three alarmins were targeted in allergen-challenged mice showed decreased chronicity of type-2 driven disease. Consequently, ascertaining the mechanism of activity of these upstream mediators has implications for understanding the outcome of targeted therapies designed to counteract their activity and alleviate downstream type 2-high and low effector responses. Furthermore, identifying the factors which shift the balance between the elicitation of type 2-high, eosinophilic asthma and type-2 low, neutrophilic-positive/negative asthma by alarmins is essential. In support of these efforts, observations from the NAVIGATOR trial imply that targeting TSLP in patients with tezepelumab results in reduced asthma exacerbations, improved lung function and control of the disease. In this review, we will discuss the mechanisms surrounding the secretion of IL-25, IL-33, and TSLP from the airway epithelium and how this influences the allergic airway cascade. We also review in detail how alarmin-receptor/co-receptor interactions modulate downstream allergic inflammation. Current strategies which target alarmins, their efficacy and inflammatory phenotype will be discussed.